Angiostrongylus cantonensis is an Important Cause of Eosinophilic Meningitis in southern Vietnam - McBride, A; Hong Chau, T; Thu Hong, N; Hoang Mai, N; To Anh, N; Tan Thanh, T; Hue Van, T; Thi Xuan, L; Manh Sieu, T; Hong Thai, L; Van Chuong, L; Xuan Sinh, D; et al. (Oxford University Press, 2017)
We utilised PCR to demonstrate that Angiostrongylus cantonensis was responsible for 67.3% of 55 cases of eosinophilic meningitis from a cohort of 1690 adult patients with CNS infection at a tertiary hospital in southern Vietnam. Longer duration of illness, depressed consciousness and peripheral blood eosinophilia were associated with PCR positivity.